Unusual presentations of branchial cyst - Hajare, Priti S.; Metgudmath, Vinita V.; Mehadi, Izhak; K., Neema; Babu, Elsa; Nayak, Dhanush (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Branchial cyst is a developmental cyst commonly presenting as a solitary, painless neck mass, typically located over lateral aspect of the neck. Most commonly located along the anterior border and the upper third of the sternocleidomastoid muscle in the anterior triangle of the neck, it is very rare for a branchial cyst to manifest in other locations. Branchial cysts are believed to be derived from the branchial apparatus, mostly from the second branchial arch, although many theories have been proposed to explain the aetiology of branchial cysts. Congenital branchial cysts of the nasopharynx originate from the lateral nasopharynx with an inferior and medial extension. This rare and unusual occurrence of the cyst is characterised by its avid mucus secretion and unilateral presentation. Here we present four different presentations of branchial cyst - as a midline swelling, an unusually large presentation, nasopharyngeal presentation. Histopathology report showed cyst lined by stratified squamous epithelium and pseudo stratified ciliated columnar epithelium at places along with subepithelial lymphocytes suggesting branchial cyst. Hence, Branchial cyst should also be taken as one of the differential diagnoses in cystic lesions of the neck and lateral cystic lesions of nasopharynx.